Development of Canva-Based Animated Video Learning Media for Geography Instruction on Natural Disaster Mitigation at SMAN 01 Sekadau - Terusiana, Elisabeth; Bahari, Yohanes; Basri, Muhammad; Warneri, Warneri; Salam, Urai (FKIP - Universitas Riau, 2026)
Disaster mitigation learning in Geography requires dynamic, spatial, and contextual conceptual understanding; however, instructional practices remain largely dominated by static media and lecture-based approaches. This study aimed to develop and evaluate the effectiveness of Canva-based animated video media integrated with the local context of Sekadau to improve students’ learning outcomes. The research employed a Research and Development (R&D) approach using the ADDIE model combined with a mixed-methods design. The subjects were eleventh-grade students at SMAN 1 Sekadau, selected through a quasi-experimental nonequivalent control group pretest–posttest design. Data were collected through interviews, documentation, expert validation sheets, student response questionnaires, and Quizizz-based learning outcome tests. The findings showed that the developed media achieved very high feasibility based on expert validation (mean scores 3.7–3.9) and positive student responses (3.6–3.8). Statistical analysis indicated a significant difference in learning outcomes between the experimental and control groups (p < 0.05), with a very strong effect size (d = 2.48). The results suggest that Canva-based animated videos effectively support students’ understanding of disaster mitigation by facilitating process visualization, spatial representation, and contextual learning integration.